The Thracian inscriptions – contributions to a new interpretation - Rasmussen, Jens Ekmegard (Balcanica Posnaniensia. Acta et studia, 1990)
The article concerns the problem of interpreting the few preserved Thracian inscriptions, which constitute a key source for the study of the almost unknown Thracian language. The problem is significant due to the limited source base and the difficulties in reading and interpreting the texts. The aim of the work is to propose a new interpretation of two of the most important epigraphic monuments: the inscription from the Ezerovo ring (5th century BC) and the inscription from the funerary slab from Kjolmen (6th century BC). The author applies linguistic methods, including paleographic analysis of signs, comparisons with Indo-European languages, and phonological and morphological reconstruction of the texts. The most important results include a revision of previous readings of signs, identification of phonetic values of certain symbols, and the proposal of a coherent interpretation of the structure of the Kjolmen text as a two-line formula of Indo-European character. The author interprets a key word as referring to a “grave cover” and reconstructs the meaning of the inscription as a funerary formula of the type: “whoever violates this grave shall be punished.” The analysis also indicates the presence of grammatical and lexical elements with clear parallels in other Indo-European languages. The conclusion is that despite the limited material it is possible to partially reconstruct the meaning of Thracian inscriptions, and that the Thracian language shows strong connections with the Indo-European family, which opens new research perspectives.